KAJIAN VISUAL LOGO CLOTHING BERDASARKAN JENISNYA - Titi Widia, - (2018)
Logo merupakansalahsatuprodukdesainkomunikasi visual karena didalamnyaterdapatkonsepkomunikasidanungkapankreatif, teknikdan media denganmemanfaatkanelemen-elemen visual ataupunrupauntukmenyampaikanpesanuntuktujuantertentu (tujuaninformasiataupuntujuanpersuasiyaitumempengaruhiperilaku). Logo jugadapatdijumpai di berbagaiproduk, salahsatunyaadalahprodukclothing. Beragamjenis logo yang dapatkitajumpaipadaprodukclothingmenjadimenarikuntukdikajikarenamasing-masingdari logo tersebutmemilikivisualisasidanmakna yang berbeda.Olehkarenaitupenelitimerasatertarikuntukmelakukanpenelitianpadabeberapa logo clothing yang dianggapmemenuhikriteriadariberbagaihalsepertisejarahpembuatan, visualisasi yang menarik, ketermudahanuntukdiingatolehmasyarakatluas, dan lain-lain.Rumusanmasalahpadapenelitianiniyaituvisualisasi yang terdapatpada logo clothingberdasarkanjenisnyayaitulogotype, logogramdanlogotyposerta makna yang disampaikanpada logo clothingberdasarkanjenisnyayaitulogotype, logogramdanlogotypo.Metode yang digunakandalampenelitianiniyaitumetodedeskriptifanalitisdenganpendekatankualitatif.Pemilihanmetodedanpendekataninibertujuanuntukmempelajarikarakteristik yang diteliti.Dasarpemikirankualitatiftidakbergantungpadakuantitastetapilebihpadakualitas yang akanditeliti. Dalampenelitiankualitatif, datayangdikumpulkandapatberupateks,dokumen, gambar,foto, artefakatauobyek-obyek lain yang ditemukan di lapanganselamapenelitiandilakukan.Hasilpenelitianmenjelaskanbahwasecara visual logo dibagiberdasarkantigajenis, yang pertamaadalah logo yang hanyamemilikiunsurtulisan/typografi (logotype) yang terdiridariclothing UNKL347, BLOODS, COSMIC, LUMO dan OUVAL RESEARCH. Logo yang hanyamemilikiunsurgambar/picture mark (Logogram) yang terdiridariclothing WADEZIG, KIDDROCK, BLACK ID, NOMITRADEMARK, dan MATERNAL. Logo yang hanyamemilikikeduaunsursekaligusyaitutulisandangambar (Logotypo) yang terdiridariclothing 3 SECOND, ZHEV, SHARKSCLOTHING, ABIGAIL dan SKATERS.Makna yang diterapkanpadasemua logo clothingberdasarkanjenisnyainisecaraumummemilikikonsep/idealisme yang hampirsama, yaitumengangkattema-temamengenaipassion, hobi, lifestyle, dankecintaanterhadapmusik. ;---Logo is one of the visual communication design products because there are communication concepts and creative expressions, techniques and media by utilizing visual elements or forms to convey messages for specific purposes (the purpose of information or the purpose of persuasion is to influence behavior). We can also find logos on various products, one of which is a clothing product. Various types of logos that we can find in clothing products, are interesting to study because each of these logos has a different visualization and meaning. Therefore, researchers feel interested in doing research on some clothing logos. The selected logo is a logo that researchers consider to meet the criteria of various things such as the history of manufacture, interesting visualization, easy to remember by the wider community, and others. The formulation of the problem in this study is visualization is found in the clothing logo based on the type, namely logotype, logogram and logotypo and the meaning conveyed in the clothing logo based on its type, namely logotype, logogram and logotypo. The method used in this study is descriptive analytical method with a qualitative approach. The selection of methods and approaches aims to study the characteristics under study. Qualitative rationale does not depend on quantity but rather on the quality to be studied. In qualitative research, the data collected can be in the form of text, documents, pictures, photos, artifacts or other objects found in the field during the study. The results of the study explain that visually the logos are divided into three types, the first is a logo that only has writing/typographic (logotype) elements consisting of UNKL347, BLOODS, COSMIC, LUMO and OUVAL RESEARCH clothing. A logo that only has a picture mark (Logogram) consisting of WADEZIG, KIDDROCK, BLACK ID, NOMITRADEMARK, and MATERNAL clothing. Logo that only has two elements at once, namely writing and drawing (Logotypo) which consists of 3 SECOND, ZHEV, SHARKSCLOTHING, ABIGAIL and SKATERS clothing. The meaning that is applied to all clothing logos based on this type generally has almost the same concept/idealism, namely raising themes about passion, hobbies, lifestyle, and love of music.